Financialisation of the transnational food chain: from threat to leverage point?. (2nd October 2018) - Ferrando, Tomaso
ABSTRACT: The 2008–2009 spike in food prices brought to the forefront the link between the transnational food system and the mechanisms of finance. However, the interconnections between food and finance go far beyond trading in futures and buying indexes and is redefining the chain from farm to fork. Having identified the main implications of a financialised food system, the article identifies two categories of legal and quasi-legal reaction that differ in objectives and processes: the approach of those who prefer engaging from within the financial paradigm and that of those who call for more stringent regulations. With the use of examples, it then reflects on the potential and limits demonstrated by each approach in engaging with the financialisation of food and suggests that complexity and interconnections of finance may become allies against unsustainable practices. The tactical use of EU Directive 95/2015 on non-financial disclosure is analysed with particular care.